Structural And Evolutionary Analysis of Zika Virus NS5 Protein - N Sujetha; K Rohini; N Mohan; Prabhu Puniethaa (BIO Web of Conferences)
The Zika virus's (ZIKV) Non-Structural (NS5) protein is an important target for developing antiviral medications and is essential to the virus's reproduction mechanism. An integrated approach to bioinformatics examines its evolutionary, dynamic, and structural features. Multiple sequence alignment and evolutionary trees are necessary for protein function. Alpha helices, beta strands, and random coils are predicted to all have significant secondary structures. Additionally, this approach predicted the three-dimensional structure of NS5, which was then refined and validated to guarantee the molecule's structural integrity. Using solvation in water and molecular dynamics (MD) simulation, the protein's flexibility and stability under physiological conditions were examined. These simulations proved valuable in gaining insights into the conformational dynamics of NS5, linking structural features to functional roles in the viral life cycle. By combining evolutionary analysis, structural modeling, and MD simulations, a comprehensive understanding of NS5’s structure-function relationship emerges, paving the way for novel antiviral therapies targeting this protein.